(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
An experiment was conducted to study the effect of cultivar and concentration of agar and gelrite on in vitro multiplication of gerbera (G.jamesonii) shoots. Sterile in vitro growing shoots of the gerbera cultivars Ameretto, Red Bull, Ruby Red, Yellowish green and Crillo were placed in glass jars containing nutrient media with different concentrations of agar and gelrite. There was a significant interaction between the gelling agents’ concentrations and the gerbera cultivars. There was a decrease in the multiplication and vitrification rates with the increase of the concentration of the different gelling agents in the nutrient medium.